Perceptions, Uses, and Attitudes Towards ChatGPT Among University Students in the Field of Education - Pattier, Daniel (Journal of Interdisciplinary Studies in Education, 2026)
Generative AI tools like ChatGPT are reshaping higher education, offering new learning opportunities while raising concerns. This study examines education students' perceptions, uses, and attitudes toward ChatGPT. A quantitative, cross-sectional design was applied with 205 undergraduate and master's students. Data were collected using a validated questionnaire (α = .92) assessing five dimensions. Non-parametric tests were used. Findings show that 90.2% have used ChatGPT, mainly for academic purposes; 82% use it to support their studies, and 23.9% admit to copying content as their own. Affective and academic dimensions received highest ratings. Significant differences appear by gender, age, academic level, year of study, economic status, and unreferenced use. The study concludes that digital literacy and institutional policies are essential for responsible AI integration in higher education.